Proceedings of the VII European Congress on Computational Methods in Applied Sciences and Engineering (ECCOMAS Congress 2016) 2016
DOI: 10.7712/100016.2316.8820
|View full text |Cite
|
Sign up to set email alerts
|

Impact of External Surroundings on Natural Convection in a Vertical Channel Asymmetrically Heated

Abstract: Abstract. This paper reports a numerical study of natural convection problem between vertical plates with asymmetric heating. Influence of perturbation conditions outside of the channel on flow structure and on the heat transfer rate are investigated. The effect of temperature consists of considering a gradient of temperature between the bottom and top of the channel in order to obtain a thermal stratification. The effect of surface radiation on the laminar air flow with a thermal stratification is investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…He showed that once the thermal stratification develops and reaches the top of the channel, the induced mass flow rate decreases. More recently Ramalingom and Bastide [29] also numerically modelled a uniformly heated channel introducing a temperature difference in the ambient fluid between the inlet and the outlet corresponding to a stable stratification in the ambient fluid. The results show as well a decrease in the induced mass flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…He showed that once the thermal stratification develops and reaches the top of the channel, the induced mass flow rate decreases. More recently Ramalingom and Bastide [29] also numerically modelled a uniformly heated channel introducing a temperature difference in the ambient fluid between the inlet and the outlet corresponding to a stable stratification in the ambient fluid. The results show as well a decrease in the induced mass flow rate.…”
Section: Introductionmentioning
confidence: 99%